2012
DOI: 10.1042/cbi20100782
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐dihydroxyvitamin D3 enhances fast‐myosin heavy chain expression in differentiated C2C12 myoblasts

Abstract: We investigated the effect of VD3 (1α,25-dihydroxyvitamin D3) on the proliferating, differentiating and differentiated phases of C2C12 myoblasts, a mouse skeletal muscle cell line. VD3 treatment in 10% FBS (fetal bovine serum) inhibited the proliferation and viability of the cells in a dose-dependent manner. It also dose-dependently increased the percentage of cells in the G0/G1 phase as shown by flow cytometry. In the differentiating phase, VD3 treatment inhibited the formation of myotubes and the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 42 publications
8
68
1
1
Order By: Relevance
“…In view of our previous results (Buitrago et al 2012), it was expected that a cell proliferative state would be observed at 24 h. This may be explained by the fact that now the cells were deprived of serum for 16 h, instead of 2 h as reported previously. Okuno et al (2012) Figure 7 Silencing of cyclin D3 by a specific siRNA affects VDR and myogenin expression in muscle cells. C2C12 WT cells were transfected with 50 pmol cyclin D3 siRNA or control siRNA for 6 h according to the manufacturer's specifications.…”
Section: Discussionmentioning
confidence: 99%
“…In view of our previous results (Buitrago et al 2012), it was expected that a cell proliferative state would be observed at 24 h. This may be explained by the fact that now the cells were deprived of serum for 16 h, instead of 2 h as reported previously. Okuno et al (2012) Figure 7 Silencing of cyclin D3 by a specific siRNA affects VDR and myogenin expression in muscle cells. C2C12 WT cells were transfected with 50 pmol cyclin D3 siRNA or control siRNA for 6 h according to the manufacturer's specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Whether vitamin D has positive effects on myoblast proliferation and differentiation is currently under debate. Recent studies [27] suggest that vitamin D treatment enhances fast type (type IIa) MyHC expression in fully differentiated C2C12 myotubes. Type II muscle fibers contain type IIa MyHC [77].…”
Section: Effects Of Ageing On Serum Concentration Of Vitamin D Mumentioning
confidence: 99%
“…However, there has been still some controversy as to whether VDR is expressed in skeletal muscle [24, 29, 32]. For example, some studies have failed to detect VDR in skeletal muscle [24, 25, 9597]; other studies have shown that VDR protein and/or mRNA are detectable in skeletal muscle [2123, 29, 46, 98] and myogenic cells [26, 27, 29, 31, 32, 42, 45, 46, 53, 55, 98104]. In brief, Wang et al [105] call into question the specificity of various commercially available VDR antibodies.…”
Section: Vitamin D Receptor Expression In Skeletal Muscle and Myogmentioning
confidence: 99%
See 2 more Smart Citations